A comprehensive index to Bag-ong Kusog 1915-1927 - Cabellon, Wilhelmina B. (1978)
This is a comprehensive index to all the issues of BAG-ONG KUSOG, a Sugbuanon newspaper, from 1915-1927. This newspaper was published in Cebu from 1915-1941 and was considered the leading periodical of its time. It reached a peak circulation of 7,000. Behind the popularity of BAG-ONG KUSOG was its publisher-editor, Vicente Rama, a prolific fiction writer and journalist and an honored public servant. This newspaper regularly provided space for literacy pieces and like the other Sugbuanon periodicals, was responsible for encouraging and fostering Sugbuanon literature.